Play along or play alone?:studies on presence, interactivity and free musical improvisation (Orfeu, 2020)
This article is composed by reflections about the concept of production of presence developed by Hans Ulrich-Gumbrecht and by the presentation of procedures that aim to approximate the concept to the practice of Free Musical Improvisation (FMI). To establish the creative process associated to Gumbrecht's conceptions, a performative proposal was developed to be performed by Orquestra Errante, a group thatresearches FMIinUniversity of São Paulo (Brazil). Among its directions, the proposal suggests that musicians improvise mediated by audio recorders and internet and then report on oscillations between sense and presence effects that have occurred during improvisations and what qualities physical presence would bring to this type of performance. The study sought, therefore, to add new tools for the creation of sound in real time and to provide reflections on the univocal relationships established between its participants, following conceptual precepts presented by Gumbrecht`s thought.
Keywords: interdisciplinary studies; performance; virtual interactivity; production of presence; Free musical improvisation